Technogenesis as a factor feature of technogenicconditioned heat supply systems in which electromagnetic fields are used in the preparation of water - Zhuravska, N. (Ways to Improve Construction Efficiency, 2019)
Modern civilization in the twenty-first century has entered a new phase of its development, when people have taken on the function of integrating their knowledge to create new nanotechnologies that are highly efficient for the economy and energy production and safe for environmental impact. The article emphasizes that the main tactical intention to ensure high efficiency of production processes and preventive production activities in construction in the process of non-reagent preparation of water in electromagnetic fields (magnetized water of heat supply systems) is the unification of organizational and management decisions in the process of operation of heat power systems (feasibility studies) in order to achieve reliable analytical information on the results of passive monitoring of material flow status of feasibility studies. The key tactical intentions of achieving high efficiency of production processes of prophylactic production activities in the process of non-reactive water treatment in electromagnetic fields (magnetized water in heating systems) are the unification of organizational and management decisions in the operation of systems of thermal power facilities (GPO) in order to achieve reliable analytical information about the results of monitoring the passive state of material flow in the systems of GDO. As the results of the studies showed, the sensitivity of the methods used to control the state of material flows of HPO systems allows to determine the dynamics of the components of material flows in time and space. According to the scientific and technical literature and personal research, the technology of using magnetized water for its preparation in heating systems is relevant and promising due to its implementation (based on experimental testing) and saving energy and material resources, as well as the formation of biological fouling. We have found that the sensitivity of the information-analytical system, which is material flows, arises in complex inorganic systems, which is a major factor in the sequence of operation of water treatment technology in electromagnetic fields (EMF). This is confirmed by the fact that the proposed analytical control system (indicator) is, with the linearity of the calibration functions, a feature of determining the concentration below which it is impossible to determine the presence of this component in the material flows.